2012
DOI: 10.1179/1351000212y.0000000003
|View full text |Cite
|
Sign up to set email alerts
|

In vivoandin vitroantioxidant activity and hepatoprotective properties of polyphenols fromHalimeda opuntia(Linnaeus) Lamouroux

Abstract: Antioxidant activity and hepatoprotective properties of the aqueous extract and tetrahydrofuran-extracted phenolic fractions of Halimeda opuntia (Linnaeus) Lamouroux were investigated in rats with chemically induced liver injury. Total polyphenols were determined by using the Folin-Ciocalteau reagent. Liver damage was induced by CCl(4) and assessed by a histological technique. Reverse transcription/polymerase chain reaction (RT/PCR) analysis showed increased superoxide dismutase (SOD) and catalase (CAT) gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 36 publications
0
13
0
2
Order By: Relevance
“…Estudos têm demonstrado efeitos benéficos do consumo de frutas, os quais têm sido atribuídos à presença de nutrientes, como as vitaminas A, C e E (DE OLIVEIRA E SILVA et al, 2012;GAO et al, 2012;WANG et al, 2012), e principalmente ao conteúdo de compostos bioativos encontrados nos vegetais (FLORES et al, 2012;LI et al, 2013). Muitos desses compostos atuam como sequestradores de radicais livres, enquanto outros agem como quelantes de metais catalisadores de reações de geração de espécies reativas de oxigênio (HALLIWELL;GUTTERIDGE, 2007;FLOEGEL et al, 2011).…”
Section: Introductionunclassified
“…Estudos têm demonstrado efeitos benéficos do consumo de frutas, os quais têm sido atribuídos à presença de nutrientes, como as vitaminas A, C e E (DE OLIVEIRA E SILVA et al, 2012;GAO et al, 2012;WANG et al, 2012), e principalmente ao conteúdo de compostos bioativos encontrados nos vegetais (FLORES et al, 2012;LI et al, 2013). Muitos desses compostos atuam como sequestradores de radicais livres, enquanto outros agem como quelantes de metais catalisadores de reações de geração de espécies reativas de oxigênio (HALLIWELL;GUTTERIDGE, 2007;FLOEGEL et al, 2011).…”
Section: Introductionunclassified
“…We observed that the treatment with the seaweed Halimeda spp led to a significant increase in the activity of these enzymes, which in turn resulted in an enhanced antioxidant defense. Mancini-Filho et al [12] reported an over-expression of catalase genes by treatment with FPA from Halimeda monile, while de Oliveira e Silva et al [14] by RT/PCR analysis showed an increase in the catalase gene expression in the group treated with free phenolic acid (FPA) fractions from Halimeda opuntia, suggesting the inductor effect of these compounds on the enzyme genes. Accordingly, Vidal et al [21] demonstrated similar effect with Halimeda incrassata.…”
mentioning
confidence: 99%
“…The antitumour effect was detected by induction of apoptosis in leukemia cells, using extracts from H. discoidea [41]. Moreover, the genus Halimeda has been studied for antioxidant properties; animal studies carried out in our laboratory have shown that Halimeda spp effectively attenuates oxidative stress exhibiting neuroprotective and hepatoprotective activities [8,9,[12][13][14]21,37,39,42] In the quest for more potent antioxidants from natural sources, our group has been especially interested in studying the beneficial properties of seaweed from the Halimeda genus for an application in biomedicine in hepato-, neuro-and athero-protection.…”
mentioning
confidence: 99%
See 2 more Smart Citations